Keragaan dan Hubungan Berbagai Komponen Hasil Tanaman Karet (Hevea brasiliensis Muell. Arg.) pada Dua Populasi Hasil Persilangan PB 260 dengan PN - , Novalina; M. Jusuf; G. A. Wattimena; , Suharsono; Aidi Daslin (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Latex yield of rubber tree (Hevea brasiliensis Muell. Arg.) is a complex trait influenced by external and internal factors. In this trial, F1 progenies of two populations (crossing PB 260 as high latex yielder x PN as low latex yielder) and their parents were used to study the characteristic of yield components, namely physiology, anatomy and growth characters which influence latex yield. Based on statistic analysis, it showed that latex yield of two populations had high variation among their F1 progenies. The other variables such as girth, bark thickness, number of latex vessel rings, plugging index, sucrose content and inorganic phosphate content also showed high variation. Based on path analysis and stepwise regression, it showed that the number of latex vessel rings and plugging index had bigger direct effect on determining latex yield of A population (PB 260 x PN 7111), while girth and plugging index variables had bigger direct effect on latex yield of C population (PB 260 x PN 7).